Effect of edible chitosan film enriched with anise (Pimpinella anisum L.) essential oil on shelf life and quality of the chicken burger - Mahdavi, Vahid (Food Sci Nutr, 2017)
In this study, the effect of chitosan film (CF) with different concentrations of anise essential oil AEO (0, 0.5, 1, 1.5 and 2%) on the quality of chicken burger during chilled storage (4 + 1°C) were examined over a period of 12 days. For this purpose, at the first, the physical and mechanical properties of the produced films were studied. Then, the chicken burger was covered with the produced films. Different treatment were analyzed by biochemical properties such as moisture and thiobarbituric acid, bacteriological properties such as total viable counts and total psychrotrophic counts, Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli. The results of this study showed that adding AEO improved the properties of CF, the moisture, solubility, and water vapor permeability decreased in these films. By increasing the concentration of AEO the tensile strength and elasticity of film were increased. CF with AEO, delayed lipid oxidation in chicken burger and improved the chemical properties of chicken burger. Also, microbial spoilage in these samples decreased significantly (p < .05) compared to the control sample. AEO at 2% in all experiments had better results than other treatments (p < .05), and the AEO (1.5% and 2%) had acceptable biochemical, bacteriological attributes up to end of storage, and these treatments could reduce the population of pathogen bacteria below the acceptable level from day 3 until the end of the storage period. Sensory score of the treatment containing AEO at 1.5% was higher than the sensory score of AEO at 2%. Overall, the results of this study showed that the use of CF with AEO as a natural preservative increased the shelf life of meat products. Considering the relatively similar anti‐oxidation and antimicrobial effect of AEO at 1.5 and 2% and also economic aspects, optimum dose for AEO could be 1.5% in the film.